Similarities and Differences in the K-13 Curriculum and the Learning Freedom Curriculum at the High School Level at SMAN 13 Pangkep - Hermawati Hermawati; Supriadi Supriadi; Nurlina Nurlina; Muhammad Fahreza W (CV. Rayyan Dwi Bharata, 2023)
This study aims to determine the similarities and differences between the K.13 curriculum and the Merdeka Belajar curriculum at the high school level at SMAN 13 Pangkep, namely by looking at the process of implementing the K. 13 curriculum and the Merdeka Belajar curriculum. The method used in this study is the Systematic Literature Review (SLR) method. The results of this study show that the similarity between the K.13 curriculum and the Merdeka Belajar curriculum is a learning objective based on the objectives of the National Education System and National Education Standards, while the difference between the K. 13 curriculum and the Merdeka Belajar curriculum is the addition of the development of the Pancasila student profile to the MerdekaBelajar curriculum.